2022
DOI: 10.3390/a15090308
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Chronic Kidney Disease: A Comprehensive Performance Analysis of Deep Learning Models

Abstract: Chronic kidney disease (CKD) is one of the most life-threatening disorders. To improve survivability, early discovery and good management are encouraged. In this paper, CKD was diagnosed using multiple optimized neural networks against traditional neural networks on the UCI machine learning dataset, to identify the most efficient model for the task. The study works on the binary classification of CKD from 24 attributes. For classification, optimized CNN (OCNN), ANN (OANN), and LSTM (OLSTM) models were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A previous study also showed that the performance of RSF (C-index: 0.965) is significantly better than conventional Cox PHM (C-index: 0.766) for 378 patients with kidney transplantation, with RSF particularly useful for intuitive variable selection [ 24 ]. Recently, Mondol achieved high accuracy in early CKD prediction using convolutional neural network, ANN, and long short-term memory models [ 25 ]. In our recent study, high performance was obtained for predicting CKD progression using random forest methods, with C-indexes of 0.96 within 5 years in the early stage and 0.97 within 1 year in the advanced stage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study also showed that the performance of RSF (C-index: 0.965) is significantly better than conventional Cox PHM (C-index: 0.766) for 378 patients with kidney transplantation, with RSF particularly useful for intuitive variable selection [ 24 ]. Recently, Mondol achieved high accuracy in early CKD prediction using convolutional neural network, ANN, and long short-term memory models [ 25 ]. In our recent study, high performance was obtained for predicting CKD progression using random forest methods, with C-indexes of 0.96 within 5 years in the early stage and 0.97 within 1 year in the advanced stage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, high performance was obtained for predicting CKD progression using random forest methods, with C-indexes of 0.96 within 5 years in the early stage and 0.97 within 1 year in the advanced stage [ 14 ]. Although the models proposed by previous studies show high performance, the quality and accuracy of the estimates may vary over time [ 24 , 25 ]. The use of time-independent covariates for individual risk variables often leads to a higher accuracy rate and overestimation percentage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become increasingly common for people to experience kidney failure, a chronic condition that can take a long time to diagnose [16]. The kidney plays an essential role in the body by filtering waste and excess fluids, and when it is damaged, it cannot effectively clean the blood, which can cause further health issues [17]. In addition to blood tests, imaging tests like ultrasounds, CT scans, and MRIs can detect structural abnormalities in the kidneys such as cysts, tumors, and obstructions [16].…”
Section: Other Testsmentioning
confidence: 99%
“…In paper [7], they proposed the deep learning algorithms CNN, ANN [16], and LSTM as three optimised versions as well as traditional CNN[17], ANN, and LSTM models to predict CKD at the primary stage. They achieved accuracies of optimized CNN, ANN and LSTM are 98.75%, 96.25%, and 98.5%, respectively where as the achieved accuracies of CNN, ANN and LSTM are 92.71%, 90.43%, and 88.51% respectively.…”
Section: Introductionmentioning
confidence: 99%